APLIKASI INTEGER PROGRAMMING UNTUK MENGOPTIMALKAN PRODUKSI TERNAK AYAM - Vera Devani (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The demand for animal protein increasing from day to day sometimes make this farm product prices more expensive because it is not balanced with sufficient production. The purpose of this study was to determine the amount of production, the constraints must be considered optimize, profit and value sensitivity to optimize solutions are reached. Integer Programming is a mathematical model of settlement that allows the results of case resolution of Linear Programming in the form of fractions converted to integers without leaving the optimization settlement. Based on research conducted retrieved group production needs to be improved is the Group III (29-31 days) of 650 tails. Improvement of the factors of production is carried out on the direct workforce of 494 hours, capacity 800 tails, 4,387.5 kg of feed use, and use of the OVD of Rp 2,176,083. With the optimization conducted obtained an increase in profit of Rp 1,385,150. The value of the shadow price (dual price) of each constraint is 0, it means the rest of utilisation of capacity will not change the value of the function is the goal.